Technology and Innovation for Cleaner and More Productive and Competitive Production - United Nations Conference on Trade; Development (United Nations, 2023)
This study examines national strategies and policies related to green technology and green innovation for cleaner, more productive, and competitive production, and the role of international cooperation, including triangular and South-South cooperation, in supporting developing countries to benefit from windows of opportunity for developing, using, adopting and adapting these frontier technologies in production processes for catching up economically and technologically.